Demand information acquisition and disclosure in a non-instantaneous deteriorating items supply chain. (July 2022) - He, Yimeng; Gong, Yeming; Hong, Xianpei
Highlights: The retailer hides high demand information but discloses low demand information. The manufacturer only benefits from information disclosure. The deterioration weakens the value of information. Abstract: While previous studies of non-instantaneous deteriorating items overlook the information acquisition and disclosure, this paper considers information acquisition and disclosure strategies in a supply chain, and models a piecewise demand rate that depends on market potential, price, and time to depict non-instantaneous deteriorating items. We study three situations: "no information acquisition", "information acquisition only", and "information acquisition and disclosure". Results show that the retailer can always improve the profits by acquiring information, and the manufacturer only benefits from information disclosure. However, the deterioration of products affects the effectiveness of information acquisition and information disclosure from several aspects. Interestingly, we find the retailer will hide high demand information but disclose low demand information. In the situation "information acquisition and disclosure", the improvement of the ability to acquire information is not always beneficial to the increment of the retailer's profit. Specifically, we find that when the ability is high, with the improvement of the ability, the increment of the retailer's profit first increases and then decreases. In this situation, because of the information disclosure, the retailer has to reduce the order quantity of non-instantaneous deteriorating items than the situation "no information acquisition", even though he does not acquire any information. Furthermore, we find that the integrated supply chain performs better than the decentralized supply chain.